ImageJ for live cell imaging: From acquisition to analysis / Dr. Zokapli Eshak and Dr. Gurmeet Kaur Surindar Singh - Eshak, Zokapli; Surindar Singh, Gurmeet Kaur (Faculty of Pharmacy, 2023)
On September 20 and 21, 2023, the Tissue Culture Laboratory and Imaging Centre at the Faculty of Pharmacy, UiTM, hosted a two-day workshop on ImageJ for Live Cell Imaging: From Acquisition to Analysis. The workshop was conducted by renowned experts in this field, Dr. Zokapli Eshak from the Faculty of Pharmacy at UiTM Puncak Alam and Dr. Anis Syamimi Mohamed from the Centre for Occupational Safety, Health, and Wellbeing (COSHaW), UiTM. The workshop was skilfully facilitated by a team of dedicated laboratory staff, namely Mdm. Norhayati Mohd Monzai, Mdm. Nurul Farhanah Misripin, Mdm. Nur Fathiah Mohd Radzi, and Ms. Masni Mohd Soberi. A total of 19 participants from various institutions attended the workshop. The programme provided a comprehensive exploration of topics related to ImageJ, focusing on the application of this powerful software in the fields of cell culture techniques and microscopy. The workshop spanned two days, offering a well-rounded learning experience for all participants. On the first day, attendees delved into the theoretical aspects of cell culture techniques, antibody principles, staining techniques, antibody design, and the fundamental principles of confocal laser scanning microscopy. This theoretical foundation laid the groundwork for the practical sessions that followed. During the practical session in the afternoon, participants had the invaluable opportunity to put their knowledge into practice. They engaged in hands-on activities, including scratch assay techniques, while adhering to essential safety guidelines for handling biological samples. Moreover, participants had the privilege of examining samples under a confocal laser scanning microscope, gaining first-hand experience in utilising this advanced imaging technology.